Word of Mouth, Brand Loyalty, Acculturation and the Turkish Ethnic Minority Group in Germany - USLU, AYPAR; DURMUŞ, BERİL (ELSEVIER SCIENCE BV, 2013)
This paper sets out to provide an evaluation of population characteristics and historical trends for immigrant Turks within the mainstream German population with a view to informing target marketing strategies aimed at this growing and important segment. The intent of this project is to explore whether there is a difference between German consumers and consumers with Turkish ethnic background in Germany in the use of brand loyalty and word-of-mouth in the mobile phone purchasing process. Additionally, the article aimed to reveal if there is any difference among Turkish consumers in Germany due to acculturation levels in terms of brand loyalty and word-of-mouth behavior during the mobile phone purchasing phase. The study shows that ethnicity plays a significant role in the mobile phone purchasing decision regarding brand loyalty and word-of-mouth behaviors. The acculturation level is an important indicator of those behaviors. The findings showed that there is a difference between Turkish and German consumers in Germany in the use of brand loyalty. In addition, low acculturated Turkish consumers tend to use word-of-mouth more compared to high acculturated Turkish consumers.
Keywords: Brand loyalty; word-of-mouth; acculturation; ethnic marketing; Germany; CONSUMER